A generic remote sensing approach to derive operational essential biodiversity variables (EBVs) for conservation planning. Issue 8 (6th August 2018) - Alleaume, Samuel; Dusseux, Pauline; Thierion, Vincent; Commagnac, Loïc; Laventure, Sylvio; Lang, Marc; Féret, Jean‐Baptiste; Hubert‐Moy, Laurence; Luque, Sandra
Abstract: The open access availability of satellite images from new sensors characterized by various spatial and temporal resolutions provides new challenges and possibilities for biodiversity conservation. Methodologies aiming at characterizing vegetation type, phenology, and function can now benefit from metric spatial resolution imagery combined with an improved revisit capability. Here, we test hybrid methods and data fusion, using very high spatial resolution (VHSR) sensors in different complex landscapes encompassing three French biogeographical regions. The methodological approach presented herein has a generic value in response to national conservation targets based on the concept of essential biodiversity variables accessed by remote sensing (RS‐enabled EBVs). We focused on deriving five RS‐enabled EBVs from natural and seminatural open ecosystems: (1) ecosystem distribution, (2) land cover, (3) heterogeneity, (4) primary productivity and (5) vegetation phenology. The challenge was to develop a method that would be technically feasible, economically viable, and sustainable in time. We demonstrated that it is possible to derive key parameters required to develop a set of EBVs from remote sensing (RS) data. The combined use of remote sensing data sources with various spatial, temporal, and spectral resolutions is essential to obtain different indicators of natural habitats. One major current challenge for an improved contribution of RS to conservation is to strengthen multiple collaborative frameworks among remote sensing scientists, conservation biologists, and ecologists in order to increase the efficiency of methodological exchange and draw benefits for successful conservation planning strategies. Résumé: La disponibilité en libre accès des images satellitaires issues de nouveaux capteurs caractérisés par diverses résolutions spatiales et temporelles offre de nouveaux défis et de nouvelles possibilités pour la conservation de la biodiversité. Les méthodologies visant à caractériser, selon le type de végétation, la phénologie et le fonctionnement peuvent maintenant bénéficier de l'imagerie à résolution métrique combinée à une capacité de revisite améliorée. Nous testons ici des méthodes hybrides et la fusion de données mobilisant des images de capteurs à très haute résolution spatiale (THRS) dans différents paysages complexes englobant trois régions biogéographiques françaises. L'approche méthodologique présentée ici a une valeur générique en réponse aux objectifs nationaux de conservation basés sur le concept de variables essentielles de biodiversité accessibles par télédétection (RS‐enabled EBVs). Nous nous sommes concentrés sur l'extraction de cinq EBVs accessibles par télédétection sur des écosystèmes ouverts naturels et semi naturels: (1) distribution de l'écosystème, (2) occupation du sol, (3) hétérogénéité, (4) productivité primaire et (5) phénologie de la végétation. Le défi était de développer une méthode qui serait techniquement faisable, économiquement viable et durable dans le temps. Nous avons montré qu'il est possible de dériver les paramètres clés requis pour développer un ensemble de variables essentielles de biodiversité à partir des données de télédétection. L'utilisation combinée de sources de données de télédétection caractérisées par diverses résolutions spatiales, temporelles et spectrales est essentielle pour obtenir différents indicateurs d'habitats naturels. L'un des principaux défis actuels pour une meilleure contribution de la télédétection à la conservation de la biodiversité est de renforcer les cadres de collaboration multiples entre les scientifiques de la télédétection, les biologistes de la conservation et les écologues afin d'améliorer l'efficacité des méthodologies et d'en tirer avantages.